Wandering among Dehnhardt's gums: The cold case of Eucalyptus camaldulensis (Myrtaceae) and other nomenclatural notes on Eucalyptus. Issue 2 (14th June 2019) - Del Guacchio, Emanuele; Bean, Anthony Russell; Sibilio, Giancarlo; De Luca, Adriana; De Castro, Olga; Caputo, Paolo
Abstract : In this contribution, we treat all the names in the genus Eucalyptus published by F. Dehnhardt, including the much‐discussed E. camaldulensis . Current opinion would suggest that Dehnhardt applied this name to a plant different from that to which the name has commonly been applied. Hence, E. camaldulensis was conserved with a conserved type. Despite this, we show that Dehnhardt's original description clearly applies to the modern delimitation of E. camaldulensis subsp. camaldulensis and that conservation of the name was not necessary. Two names are neotypified on the basis of material preserved in NAP and W: E. gigantea, and E. procera . These two names are confirmed to be synonyms of other currently accepted names. Eucalyptus pulchella (of which E. linearis is a synonym) is also neotypified. A second‐step lectotypification is provided for E. globulus .